Performance on the Iowa Gambling Task in a Sample of Hypersexual Men. - Mulhauser, Kyler R. W.; Struthers, William M.; Hook, Joshua N.; Pyykkonen, Benjamin A.; Womack, Stephanie D.; MacDonald, Mark (Sexual Addiction & Compulsivity)
Executive dysfunction, characterized by impaired decision making and impulsivity, has been suspected among individuals seeking treatment for hypersexuality, yet few studies have formally investigated this topic. The present study used the Iowa Gambling Task (IGT), an objective neuropsychological instrument, and the Barratt Impulsiveness Scale (BIS), a self-report measure, to assess decision-making characteristics and impulsivity in a sample of hypersexual men. Treatment-seeking males with clinically elevated scores on the Hypersexual Behavior Inventory (HBI-19) and who otherwise met criteria for hypersexuality completed the IGT and BIS. Results were compared to a control condition. The current analysis identified significant group differences on the IGT and the BIS. Hypersexual participants selected decks containing frequent loss penalties at a greater frequency than controls on the IGT and endorsed elevated levels of impulsivity on the BIS. The current results reflect non-normative responses on both measures and are consistent with a pattern of executive dysregulation in hypersexual individuals.